2023
DOI: 10.3390/app13137759
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Laws of Stress–Energy and Progressive Damage Mechanisms of Surrounding Rock Induced by Mining Disturbance

Abstract: The rock burst induced by the mutual disturbance of mining and excavation is significantly influenced by high static load stress and external dynamic load disturbance. In this paper, the evolution characteristics and progressive damage mechanism of surrounding rock in the process of mutual disturbance of mining and excavation are systematically studied. The results show that the evolution of surrounding rock stress can be roughly divided into three stages: rapid rise in the early stage, continuous rise and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The mechanical numeri-cal calculation methods of rock mass with defects are mainly divided into three kinds: finite element method (FEM) [20,21], boundary element method (BEM) [22,23], and discrete element method (DEM) [9,24,25]. Previous studies have shown that parallel bonding modeled by the particle flow code (PFC2D) under uniaxial compression conditions is consistent with laboratory testing phenomena [14] in simulating rock cracking results [26][27][28]. Although PFC2D can only be performed on a 2D planar scale, it can be used to simulate many problems in rock engineering: crack propagation and coalescence of brittle rock materials [29][30][31].…”
Section: Introductionmentioning
confidence: 82%
“…The mechanical numeri-cal calculation methods of rock mass with defects are mainly divided into three kinds: finite element method (FEM) [20,21], boundary element method (BEM) [22,23], and discrete element method (DEM) [9,24,25]. Previous studies have shown that parallel bonding modeled by the particle flow code (PFC2D) under uniaxial compression conditions is consistent with laboratory testing phenomena [14] in simulating rock cracking results [26][27][28]. Although PFC2D can only be performed on a 2D planar scale, it can be used to simulate many problems in rock engineering: crack propagation and coalescence of brittle rock materials [29][30][31].…”
Section: Introductionmentioning
confidence: 82%